PENGARUH RETURN ON ASSET DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2022 - Ramadhan, Syahrul; Mardiati, Dijan (Journal of Research and Publication Innovation, 2024)
This study aims to analyze the effect of Return On Asset and Net Profit Margin on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2022. This research is a quantitative. Data sources obtained through the official website of the Indonesia Stock Exchange during 2017-2022. With a population of 26 companies in the food and beverage sub-sector and 11 companies were used as a research sample. The data analysis method in this study uses a penel data test, a classical assumption test, a hypothesis test, a determination coefficient (R2), and multiple linear regression using the Eviews version 12 approach, the results of the Return On Asset research on stock price are known to be calculated as 4.471774 > 1.997730 ttable with a significance level of 0.0000 < 0.05, then, H1 is accepted which means that the Return On Asset variable has a significant effect on the Stock Price. From the results of the Net Profit Margin analysis of the stock price, it is known that the calculation is -0.680751 < 1.997730 tables, and obtained a significance level of 0.4985 > 0.05, then H2 is rejected which means that the Net Profit Margin variable does not have a significant effect on the stock price.while simultaneously obtained a value of 25.61655 and a table of 3.14 with a significance level of 5% In this case, the calculation is 25.61655 > 3.14 table of probability level of 0.000000 < 0, 05 then it can be concluded that H3 is accepted, which means that return on and Net Profit Margin simultaneously have a significant effect on the stock price.